Analysis of MI Teachers' Pedagogical Competencies In Digital Fiqh Learning In The Alpha Generation At MI Assamarqondi Palang - Achmad Fastabikhul A'mal; Akhmad Aji Pradana; Nahid Faza Fachory (Edu-MI Al Hikmah: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2026)
Digital technology has dramatically changed the world of education, including the way Islamic Jurisprudence (Fiqh) is taught in Islamic Elementary Schools (MI). As a digital native, the Alpha generation focuses on visual, interactive, and technology-based learning. In this situation, teachers must have pedagogical skills that enable them to adapt their learning to technological advances and the characteristics of their students. However, digital-based Islamic Jurisprudence learning still faces many challenges. Some of these include limited digital learning resources and teachers' lack of digital literacy. The purpose of this study was to evaluate the pedagogical skills of MI teachers in digital-based Islamic Jurisprudence learning for the Alpha generation at Palang MI Assamarqondi. In this study, a qualitative approach was used, and this type of research was descriptive. Data were collected through documentation, interviews, and observations with informants: Islamic Jurisprudence teachers, the principal, and students. Using the Miles and Huberman model, data analysis involved data reduction, data presentation, and drawing conclusions. The results showed that teachers used their pedagogical skills to understand students' characteristics, plan and implement digital-based learning, assess learning, and develop students' potential. With the use of digital media such as instructional videos, student interest and engagement in Islamic jurisprudence learning can increase. However, due to limited supporting facilities and teachers' ability to use this technology, digital-based Islamic jurisprudence learning has yet to achieve optimal success. Therefore, ongoing support for digital learning tools and training for teachers is needed